THE ROLE OF RESILIENCE ON MENTAL AND HEALTH AWARENESS: A SURVIVAL EXPERIENCE AMIDST COVID 19 IN THE PHILIPPINES - Dr. Froilan D. Mobo; Dariarie Ricardo; Carol Tripolca; Mirasol Abad; Jesus Arenas Jr (Scholar Express Journal, 2021)
There are so many potential risk factors which include job not secured which resulted to negative impact on one's daily income during the pandemic crisis, lack of confidence in one's capacity to get rid of the contracting from the virus and comply with the preventative policies set by the Inter-Agency Task Force on COVID 19 (ITAF) by following the strict compliance with social distance measures, wearing of face mask and face shield which can be result from / of mental and health well-being. The purpose of the study is to know the important role of Resiliency on Mental and Health awareness and to know how to deal with COVID-19 pandemic and their stress-cop strategies or other factors that may implicate the spreading of the virus, and other challenges related to COVID 19 in San Narciso, Zambales, Philippines. The researchers recommend an intervention program to prevent from experiencing resilience on mental and health like engagement in online activities like work from home or other activities that can be done while at home
Keywords: Resilience; Mental; Health; Awareness